2018
DOI: 10.1186/s40360-018-0200-y
|View full text |Cite
|
Sign up to set email alerts
|

A randomised, double-blind, placebo-controlled phase 1 study of the safety, tolerability and pharmacodynamics of volixibat in overweight and obese but otherwise healthy adults: implications for treatment of non-alcoholic steatohepatitis

Abstract: BackgroundAccumulation of toxic free cholesterol in hepatocytes may cause hepatic inflammation and fibrosis. Volixibat inhibits bile acid reuptake via the apical sodium bile acid transporter located on the luminal surface of the ileum. The resulting increase in bile acid synthesis from cholesterol could be beneficial in patients with non-alcoholic steatohepatitis. This adaptive dose-finding study investigated the safety, tolerability, pharmacodynamics, and pharmacokinetics of volixibat.MethodsOverweight and ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 41 publications
(36 reference statements)
1
12
0
Order By: Relevance
“…32 Phase I studies have demonstrated that volixibat is not metabolized, is minimally absorbed and is effective at reducing serum cholesterol in overweight and obese adults. 18,26,27 The increases in faecal BA excretion and serum C4 levels observed in these phase I studies support the proposed mechanism of action of volixibat in patients with NASH. It is also important that volixibat was found to reduce fasting glucose levels significantly compared with placebo in patients with type 2 diabetes mellitus (T2DM) 26 because there is a close association between NASH and T2DM.…”
Section: Introductionsupporting
confidence: 55%
See 1 more Smart Citation
“…32 Phase I studies have demonstrated that volixibat is not metabolized, is minimally absorbed and is effective at reducing serum cholesterol in overweight and obese adults. 18,26,27 The increases in faecal BA excretion and serum C4 levels observed in these phase I studies support the proposed mechanism of action of volixibat in patients with NASH. It is also important that volixibat was found to reduce fasting glucose levels significantly compared with placebo in patients with type 2 diabetes mellitus (T2DM) 26 because there is a close association between NASH and T2DM.…”
Section: Introductionsupporting
confidence: 55%
“…21,22 Consistent with this mechanism of action, increases in serum levels of 7a-hydroxy-4-cholesten-3-one (7aC4, also known as C4; a biomarker of BA synthesis) and decreases in serum cholesterol levels are observed following administration of ASBT inhibitors, including volixibat. [23][24][25][26][27] In the treatment of NASH, volixibat may reduce the pathogenic accumulation of cholesterol in the liver by reducing the levels of BAs returning to the liver via enterohepatic recirculation and by stimulating de novo production of BAs from free cholesterol in the liver and serum. This may have therapeutically beneficial anti-inflammatory, anti-steatotic and antifibrotic effects.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there are several ASBT inhibitors in development, though none have been approved by the FDA as of this writing. In addition to their potential for lowering plasma LDL cholesterol (see above), these small molecule inhibitors have shown promise in preclinical and clinical studies for the treatment of chronic constipation (65,78,276,348), NASH (289,310), type 2 diabetes mellitus (71,249,379,426), and cholestatic pruritus (24,153,264). It will be interesting to see how these promising drug candidates fare in future clinical trials.…”
Section: Substrate Specificity Of Asbtmentioning
confidence: 99%
“… 95 Volixibat, an apical sodium-dependent bile-acid transporter inhibitor, was shown as safe and tolerable among overweight and obese healthy individuals. 96 In fact, volixibat was selected for fast track by the US Food and Drug Administration and a phase II clinical trial was underway to detect its efficacy among patients with NASH, with a primary endpoint of improvement in NAFLD activity score without worsening of fibrosis. 94 However, just recently, the phase II trial for volixibat was discontinued, without any further explanation for the possible causes.…”
Section: The Current Approach To Nonalcoholic Steatohepatitis Treatmementioning
confidence: 99%